Let's breakdown the process to determine what among the 5 procedures was being applied to simplify the equations.
A.) From 6x + 9 = 4x - 3 to 2x + 9 = -3
By applying the inverse property of addition, we get,
![\text{ 6x + 9 = 4x - 3 }\rightarrow\text{ 6x + 9 - 4x = 4x - 3 -4x}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5yhqkkp44jrm0vouov4soelfhym132j56b.png)
![\text{ 2x + 9 = -3}](https://img.qammunity.org/2023/formulas/mathematics/high-school/8sslw28gguuchu95g8jo1p0v01syp7jkli.png)
Thus, for 6x + 9 = 4x - 3 to become 2x + 9 = -3, we add -4x to both sides.
Number 4 is the procedure being applied.
B.) From -4(5x - 7) = -18 to 5x - 7 = 4.5
By applying the inverse property of multiplication, we get,
![\text{ -4(5x - 7) = }-18\text{ }\rightarrow\text{ }\frac{-4(5x\text{ - 7)}}{-4}\text{ = }(-18)/(-4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/a9kbnwm5j6hnq9cjhu6fh59wb2vor6z1pz.png)
![\text{ 5x - 7 = 4.5}](https://img.qammunity.org/2023/formulas/mathematics/high-school/yobusm5od11hywv1i965llxzm2gmsvj305.png)
Thus, for -4(5x -7) = -18 to become 5x - 7 = 4.5, we multiply both sides by -1/4.
Number 1 is the procedure being applied.
C.) From 8 - 10x = 7 + 5x to 4 - 10x = 3 + 5x
We add -4 to both sides,
![\text{ (8 -10x) - 4 = (7 + 5x) - 4 }\rightarrow8\text{ - 10x - 4 = 7 - 5x - 4}](https://img.qammunity.org/2023/formulas/mathematics/high-school/sp6hul6dz5iqz3duzv1vcuw8fijyejdphh.png)
![\text{ 4 - 10x = 3 + 5x}](https://img.qammunity.org/2023/formulas/mathematics/high-school/dmfq5svfay4nt9ftrdruyupdtnp52ocmsw.png)
Thus, Number 5 is the procedure that must be applied.
D.) From (-5/4)x = 4 to 5x = -16
Applying the inverse property of multiplication, we get
![\text{ }(-5)/(4)x\text{ = 4 }\rightarrow\text{ (-}(5)/(4)x)(-4)\text{ =}4(-4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/za1y2pnte6sejypnukb7kpbmxexe57948o.png)
![\text{ 5x = -16}](https://img.qammunity.org/2023/formulas/mathematics/high-school/s93a4z2s3k9t87ltz6e6r1gned9l8s4krl.png)
Thus, for (-5/4)x = 4 to become 5x = -16, we multiply both sides by -4.
Thus, Number 2 is the procedure the must be applied.
E.) From 12x + 4 = 20x + 24 to 3x + 1 = 5x + 6
Let's apply procedure Number 3 if it is the right one to be applied. We get,
![\text{ 12x + 4 = 20x + 24 }\rightarrow\text{ (12x + 4)(}(1)/(4))\text{ = (20x + 24)(}(1)/(4))](https://img.qammunity.org/2023/formulas/mathematics/high-school/ri6h7h92yda9mn4bv9yam1q0tzpk7xln6o.png)
![(12)/(4)x\text{ + }(4)/(4)\text{ = }(20)/(4)x\text{ + }(24)/(4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/esuyob18j4weavumubo92uptdtf10od8ko.png)
![\text{ 3x + 1 = 5x + 6}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2opzad2uvoemcwdfy173f8cu903kufeesv.png)
Thus, Number 3 is the procedure that must be applied.